Penerapan Business Intelligence dalam Analisis dan Visualisasi Tren Bencana Alam Menggunakan Tableau - Murti, Aqmal Bastian; Irwansyah, Irwansyah (TIN: Terapan Informatika Nusantara, 2025)
DKI Jakarta is highly vulnerable to natural disasters due to geographical conditions, high population density, and the impact of climate change. Recurring disasters such as floods, fires, landslides, fallen trees, and tornadoes demand an effective data management and visualization system. This study applies Business Intelligence (BI) using the Tableau platform to analyze and visualize disaster trends in DKI Jakarta from 2018 to 2024. A total of 413 incident records were collected from Satu Data Jakarta and Satu Data Indonesia. The research involved ETL (Extract, Transform, Load) processes, data validation, and the development of interactive dashboards. The visualization presents key information such as disaster types, number of victims, incident locations, and yearly trends. The analysis revealed that South Jakarta recorded the highest fatalities (40,325), followed by East Jakarta (38,550). Tableau’s interactive features enable clear and accessible data presentation through charts, maps, and diagrams, supporting evidence-based decision-making. The implementation of BI successfully simplifies complex data and assists stakeholders—both government and the public—in comprehending disaster patterns. This approach offers a strategic solution for enhancing disaster preparedness, formulating effective mitigation policies, and increasing public awareness of environmental risks.